Relatioship between media convergence and user experience in two Colombian creative initiatives (2014)
Nowadays media convergence is defined as an information flow in which multiple platforms and industries take part in a process that is coming to the forefront for everyone. Therefore, audience participation is fundamental because their migratory behavior in search for entertainment, is the motor of convergence and represents a cultural change that connects apparently dispersed contents. This paper aims a reflection in relation between media convergence and user experience in two Colombian initiatives: "360 reports"-El País Newspaper (Cali) and "En óbitra" transmedia cultural magazine of the state TV station Señal Colombia". This is made based on thoughs by thinkers such as Henry Jenkins, Carlos Scolari, Arlindo Machado, Graham Meikle, Sherman Young, and Yo Jong Park. As a main conclusion, this paper shows the prosumer's empowerment process, which make the producer's and designer's job a greater one at the moment of building narratives to be told through different media.